Peningkatan Kemampuan Motorik Halus Melalui Kegiatan Mewarnai Gambar di TK Mentari Desa Batu Batu Nampar: Improving Fine Motor Skills Through Coloring Activities at Mentari Kindergarten, Batu Nampar Village - Husnul Laili (Pendidikan Al-Gafari, 2025)
Early childhood refers to the age group of children from birth to approximately six or seven years of age. This age range is also often known as the preschool period. This study aims to improve children's fine motor skills through coloring activities in group B of Mentari Kindergarten. Fine motor skills are very important to support children's development to the next level of education. Basically, motor development in children includes gross motor skills and fine motor skills. This study uses a qualitative research type, with the research subjects being teachers and students, and the object of research is children's fine motor skills. The data collection tools that the author used in this study were Observation, Interviews, and Documentation. As a conclusion, the researcher can conclude regarding the Improvement of Children's Fine Motor Skills Through Coloring Activities in group B of Mentari Kindergarten, it is known that out of 20 children, there are 2 children who have not yet developed, 3 children are starting to develop, 14 children are developing according to expectations, and 1 child is developing very well with a percentage of BB 10%, MB 15%, BSH 70%, and BSB 5%. So it can be concluded that coloring activities can improve children's fine motor skills in group B of Mentari Kindergarten.